Profiles of Facilities and Students’ Responses in Supporting Implementation of Raspberry Pi-Based Bifocal Modeling Physics Practicum - Sunardi Sunardi; Andi Suhandi; Muslim Muslim (Jurnal Pendidikan Fisika, 2023)
This research has been conducted to seek overviews of facilities and students’ responses in supporting the implementation of Raspberry Pi-based bifocal modeling physics practicum. This research was a qualitative case study done in a senior high school in Bandung District, Indonesia. The subjects of this research were two physics teachers and seventy-nine of students enrolled in tenth, eleventh, and twelfth grades in the academic year of 2020/2021. The data collection in this research was carried out through observation, interviews, and questionnaire. Observation and interviews activities were focused on laboratory room, laboratory equipment, computer laboratory, and internet facilities to obtain adequate information due to facilities which is potential to support the implementation of Raspberry Pi-based bifocal modeling physics practicum based on the technical specification of the latest Raspberry Pi found in the Indonesian market, i.e. Raspberry Pi 4 Computer Model B. Questionnaire was used to reveal the responses of students in receiving the implementation of Raspberry Pi-based bifocal modeling physics practicum and facilities owned by students which may be used to support the implementation of Raspberry Pi-based bifocal modeling physics practicum. Based on the data analysis, it was concluded that: 1) the school facilities are possible to support the implementation of Raspberry Pi-based bifocal modeling physics practicum in terms of facilities due to the computer modeling/ digital part of bifocal modeling physics practicum, 2) most students own smartphones and laptops/ computers which are possible to be utilized as output peripherals for displaying visualized physics phenomena and simulated physics data from Raspberry Pi-based bifocal modeling physics practicum devices, 3) students are willing to accept the implementation of Raspberry Pi-based bifocal modeling physics practicum in physics learning; they consider that such implementation can improve the quality of physics learning, improve the motivation of students to learn physics, and help students to easily understand physics concepts.